Exploiting Privacy-Policy and -Management Features on Social Networks: A User's Perspective - Mohd Ishak, Ismail; Rahman, Md. Arafatur; Azad, Saiful (IEEE, 2016)
A social network is a type of media that allows users to engage social interaction in the cyber world. Nowadays, this network becomes a backbone of the digital communication world as it transformed the way of information being shared across the different communities. Exploiting this network, people can easily share huge volume of information (e.g., text, audio and video) without paying any charge that runs to gain overwhelming popularity of it. Nevertheless, it is an important issue for the users to select the privacy options for their information, resulting in the decision making on who can access the information and how the information should be used. This decision can be made via privacy management features within the social networks' applications. However, the lack of study to explain the perceived use of privacy policies and management features, among social networks' users, has conjured up the significant concerns about how social network users felt about the use of these features in social networks. To address this issue, in this paper, an empirical study has been conducted to seek for users' feedbacks on the use of existing privacy policies and management features of social networks. These feedback assist in improving further the social network users' privacy features.